PENGARUH PENGGUNAAN KETERAMPILAN GURU MENJELASKAN TERHADAP HASIL BELAJAR FISIKA MATERI POKOK TERMODINAMIKA SISWA DI KELAS XI SMA NEGERI 1 SIPIROK - Sari Wahyuni Rozi Nasution (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2023)
The aim of this research was to know whether there was any significant influence of using explanation skill toward physic achievement in thermodynamic subject at the eleventh grade students of SMA Negeri 1Sipirok. The method of this research was descriptive approach by applying correlational. Sample of this research was 42 students which were taken by using random sampling technique from 126 students. Based on descriptive analysis, the average of using explanation skill was 3.2, it was categorized “good” and the average of physic achievement in thermodynamic subject was 79, it was categorized “good”. Based on statistic inferential analysis by using r product moment, it could be gotten rcount= 0.528 and r table = 0.304 at error level 5%. It could be seen that rcountis greater than rtable(0.528>0.304). It means alternative hypothesis was accepted. In the otherwords, there was any significant influence of using explanation skill toward physic achievement in thermodynamic subject at the eleventh grade students of SMA Negeri 1Sipirok.